The ClpX heat-shock protein of Escherichia coli, the ATP-dependent substrate specificity component of the ClpP-ClpX protease, is a novel molecular chaperone. - Wawrzynow, A (1995)
All major classes of protein chaperones, including DnaK (the Hsp70 eukaryotic equivalent) and GroEL (the Hsp60 eukaryotic equivalent) have been found in Escherichia coli. Molecular chaperones enhance the yields of correctly folded polypeptides by preventing aggregation and even by disaggregating certain protein aggregates. Previously, we identified the ClpX heat-shock protein of E. coli because it enables the ClpP catalytic protease to degrade the bacteriophage lambda O replication protein. Here we report that ClpX alone possesses all the properties expected of a molecular chaperone protein. Specifically, it can protect the lambda O protein from heat-induced aggregation, disaggregate preformed lambda O aggregates, and even promote efficient binding of lambda O to its DNA recognition sequence. A lambda O-ClpX specific protein-protein interaction can be detected either by a modified ELISA assay or through the stimulation of ClpX's weak ATPase activity by lambda O. Unlike the behaviour of the major DnaK and GroEL chaperones, ClpX requires the presence of ATP or its non-hydrolysable analogue ATP-gamma-S for efficient interaction with other proteins including the protection of lambda O from aggregation. However, ClpX's ability to disaggregate lambda O aggregates requires hydrolysable ATP. We propose that the ClpX protein is a bona fide chaperone, whose biological role includes the maintenance of certain polypeptides in a form competent for proteolysis by the ClpP protease. Furthermore, our results suggest that the ClpX protein also performs typical chaperone protein functions independent of ClpP.